Comparison of the retention of quartz fiber post in root canals filled with gutta-percha or Resilon - Ezatollah Jalalian; Mona Sadegh; Niaz Bazghale; Shahrzad Sadat Javadpour (Tehran University of Medical Sciences, 2012)
Background and Aims: Adequate retention of the post is a prerequisite for the clinical success which might be affected by the type of root canal filling material. The aim of this in vitro study was to compare the effects of gutta-percha and Resilon on retention of quartz fiber posts.Materials and Methods: In this experimental study, 44 maxillary central incisors were sectioned at the CEJ level and prepared endodontically using ProTaper rotary files. The specimens were then randomly assigned into two experimental groups (n=22): group R, the root canals obturated with Resilon; and group G, the root canals obturated with gutta-percha. After preparing the post space and insertion of quartz fiber posts, the coronal 10 mm of the root was sectioned perpendicular to the long axis to produce disks of 2.3 mm thickness.Then the specimens were submitted to the push-out test (1mm/min) using a universal testing machine. The data were analyzed using Mann-Whitney U test.Results: There was a significant difference between the retention of posts in groups R (7.08±5.1) and G (4.8±3.3) (P=0.04).Conclusion: Quartz fiber posts showed significantly higher retention in teeth obturated with Resilon compared to those obturated with gutta-percha.